Peningkatan Kepedulian Mahasiswa kepada Masyarakat Pesisir melalui Kegiatan Bakti Sosial - Nopiana, Medi; Rahman, Rahman; Taufiqurahman, Endang; Suartini, Sri; Anita, Widya Febryari (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2025)
The high vulnerability and damage to the coastal areas of Karawang Regency, including the impact of coastal erosion, has further exacerbated the region's high poverty level. For this reason, Universitas Singaperbangsa Karawang and other universities took the initiative to organize community service in the form of social service activities involving students with various designed objectives. Firstly, this activity is expected to help with the problems faced by coastal communities in Karawang Regency. Secondly, this activity educates students to increase their concern for fellow human beings, especially coastal communities. Thirdly, this activity is expected to improve the image of Universitas Singaperbangsa Karawang in the looks of the people of Karawang Regency through its contribution to providing solutions to various problems the community faces. This activity was accomplished well, collaborating with various parties, particularly the apparatus of Sedari Village, Cibuaya Subdistrict, Karawang Regency.